KORELASI ANTARA HASIL BELAJAR KITAB SAFINATUN NAJAH DENGAN PELAKSANAAN IBADAH MAHDHAH SHALAT SANTRI KELAS II MADRASAH DINIYAH HIDAYATUL MUBTADI’IN DESA GOWONG KECAMATAN BRUNO KABUPATEN PURWOREJO - Mudlofir, Naimah; Lestari, Prawidya (STAINU Purworejo, 2020)
Faith and piety do not go away from prayer education which is a great benefit to life. Prayers can prevent profanity and rebellion, prayer improves discipline in daily life, prayers open the heart to truth and many more benefits of prayer in the spirit. Thus prayer becomes a fundamental measure for measuring the quality of one's faith. So prayers need to be learned, known properly and practiced regularly. For the benefit to be truly felt in everyday life. This type of research is field research with a quantitative approach. Data collection techniques using values and questionnaires. Data analysis techniques using Pearson Product Moment correlation formula. The learning outcomes of the Safinatun Najah class II santri in the Diniyah Hidayatul Mubtadi'in Madrasah, Gowong Village, Bruno District, Purworejo Regency, are included in the